2016
DOI: 10.1038/srep21400
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Structure Heights and Opening Angles of Micro- and Nanocones on the Macroscopic Surface Wetting Properties

Abstract: We discuss the influence of surface structure, namely the height and opening angles of nano- and microcones on the surface wettability. We show experimental evidence that the opening angle of the cones is the critical parameter on sample superhydrophobicity, namely static contact angles and roll-off angles. The textured surfaces are fabricated on silicon wafers by using a simple one-step method of reactive ion etching at different processing time and gas flow rates. By using hydrophobic coating or hydrophilic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
55
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 46 publications
4
55
0
Order By: Relevance
“…For the master structure, we use a Si nanograss texture. 26 The nanograss was originated in Si by reactive ion etching (RIE). RIE can be used for maskless texturing of silicon surfaces through the combined effect of a corrosive gas (SF 6 and/or CH 4 ) and a passivating gas (O 2 ).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…For the master structure, we use a Si nanograss texture. 26 The nanograss was originated in Si by reactive ion etching (RIE). RIE can be used for maskless texturing of silicon surfaces through the combined effect of a corrosive gas (SF 6 and/or CH 4 ) and a passivating gas (O 2 ).…”
mentioning
confidence: 99%
“…On the microscopic level, the wetting of such surfaces can be characterized according to the degree of water intrusion into the structures. 26,43,44 The data in Figure 3c indicate a transition to an enhanced dewetting state roughly at = 325 nm. In a previous publication we found that the wetting properties for superhydrophobic surfaces with cone shaped structure depends on the opening angles of cones, rather than their heights.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The structures are produced by reactive ion etching (RIE) through the combined effect of an etching gas (SF 6 and/or CH 4 ) and a passivating gas (O 2 ) [44][45][46]. Hitherto, no investigation has been carried out with RIE for the creation of large-area nanostructures within microchannel.…”
Section: Introductionmentioning
confidence: 99%